Handwashing with Soap Education as an Effort to Foster Clean and Healthy Living Behavior among Elementary School Students Based on the Sustainable Development Goals: Edukasi Cuci Tangan Pakai Sabun sebagai Upaya Pembiasaan Perilaku Hidup Bersih dan Sehat pada Siswa Sekolah Dasar Berbasis Sustainable Development Goals - Joan Nando Pratama; Rika Yuliwulandari; Indiarto Prihadi; Ikbar Bagus Permana; Mochammad Firman Maulana; Reprilivio Ashabul Kahfi; Adit Khoirul Aziz (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Clean and Healthy Living Behavior (PHBS) is an essential foundation for improving the health status of school-aged children. One of the most effective and easily implemented PHBS practices is handwashing with soap (HWWS), particularly in elementary school settings. This community service activity aimed to enhance elementary school students’ knowledge, attitudes, and skills in practicing HWWS in accordance with national health standards. In addition, the activity was designed to support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 3 (Good Health and Well-being) and Goal 6 (Clean Water and Sanitation). The activity was conducted at SDN Medokan Ayu 1 Surabaya, targeting Grade 2B students, using initial observation, interactive education, demonstration, and direct practice of the six steps of HWWS based on the guidelines of the Indonesian Ministry of Health. The results indicated an improvement in students’ ability to correctly and sequentially perform HWWS, which has the potential to foster clean and healthy habits from an early age. Thus, this activity contributes to promotive and preventive efforts in child health and strengthens the role of higher education institutions in sustainable health development.